Ion Cyclotron Resonant Absorption Lines in ELF Hiss Power Spectral Density in the Low‐Latitude Ionosphere. Issue 2 (23rd January 2020) - Chen, Lunjin; Pfaff, Robert; Heelis, Roderick; Boardsen, Scott; Xia, Zhiyang
Abstract: The effects of multiple ion species have been observed in electromagnetic wave spectra in both the ionosphere and the magnetosphere. Here we report an event from Communication/Navigation Outage Forecast System satellite, showing a new imprint of various ion species in observations of extremely low frequency (ELF) hiss wave spectra near the equatorial ionosphere, which presents minima in the power spectral density at gyrofrequencies and their harmonics of multiple ion species (e.g., O + and He + ). Cyclotron harmonic resonant absorption is proposed to account for the observed spectral and polarization properties. Furthermore, the implication of using those wave power spectral minima to identify minor ion species in the ionosphere is discussed. Key Points: An event of wave intensity minima for the equatorial ELF waves at multiple ion cyclotron frequencies and harmonics is reported Those minima can be explained ion cyclotron harmonic absorption for oblique propagation with respect to the background magnetic field Waveform analysis shows polarization and propagation characteristics consistent with the proposed mechanism